Housing Behaviour of Urban Migrants Occupying Ngindung Lands in Yogyakarta - Astuti, Wahyu Kusuma (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2017)
This article seeks to explore the housing behavior of urban migrant and re-theorize Turner’s model on housing priority by linking it with the housing career of urban migrants in a particular locality and condition of land occupancy. The study is aimed at investigating housing priority and career of urban migrants occupying ngindung land in Yogyakarta through comprehensive quantitative analysis with crosstab technique. Five ngindung communities in Kelurahan Pringgokusuman were examined in this study. The research finding demonstrates that Turner’s model is irrelevant to explain the middle-income migrants’ behavior in choosing moderate standard housing but not maintaining proximity to jobs in the city as their income increases. This is argued to have several rationalities including their circular-mobility behavior and willingness to pay more transportation cost to workplace. Besides, homeownership is found to have no correlation with increase of income. It is therefore suggested that security for urban poor migrants is more about opportunity of livelihood rather than accumulation of assets. In conclusion, this research reflects on the limitation and uncertainty of housing options for urban poor migrants and suggests a radical shift from perceiving ‘housing as a product’ to ‘housing as a process’ –  of becoming along with the livelihood betterment of a community.Keywords: Housing priority, housing behaviour, urban migrants, ngindung occupancy